Different Markets, Different Choices: Halal Certified Chicken Consumption Among Muslims in Taiwan and Indonesia - Poppy Wulandari; Dita Kartika Sari Hasibuan; Putri Sosanti Sembiring; Ade Rasinta Herli Kristiani Purba; Grace Desy Hanatasha Ginting (LP2M IAIN Palopo, 2025)
Purpose: This study investigates differences in purchasing decisions for halal-certified chicken between Muslim consumers in Indonesia and Taiwan. It explores the socio-cultural, institutional, psychological, and economic factors shaping consumer choices, while assessing the role of halal literacy and certification. Methods: A qualitative comparative design was applied, using semi-structured interviews with Muslim consumers in both countries. Purposive sampling was conducted in Indonesia, while snowball sampling was employed in Taiwan due to the smaller and dispersed Muslim population. Data were analyzed thematically with NVivo and ATLAS.ti, supported by secondary sources such as halal regulations and community initiatives. Results: Findings reveal that Indonesian consumers often rely on trust-based relationships with Muslim vendors and assume halalness as a cultural default, reducing the urgency of certification. In contrast, Taiwanese consumers emphasize halal logos and certification bodies as primary assurances of Sharia compliance and food safety. Affordability and social familiarity drive Indonesian preferences, while availability, institutional trust, and diaspora support dominate in Taiwan. Implications: The study highlights that halal consumption is influenced not only by religious obligations but also by broader socio-cultural and institutional contexts. Results underscore the need for stronger halal assurance for fresh products in Indonesia and wider distribution of halal-certified foods in Taiwan, offering insights for policymakers and future research on Muslim consumer behavior across different settings.